2022
DOI: 10.3390/cells11162607
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Impairment: A Common Motif in Neuropsychiatric Presentation? The Link to the Tryptophan–Kynurenine Metabolic System

Abstract: Nearly half a century has passed since the discovery of cytoplasmic inheritance of human chloramphenicol resistance. The inheritance was then revealed to take place maternally by mitochondrial DNA (mtDNA). Later, a number of mutations in mtDNA were identified as a cause of severe inheritable metabolic diseases with neurological manifestation, and the impairment of mitochondrial functions has been probed in the pathogenesis of a wide range of illnesses including neurodegenerative diseases. Recently, a growing n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 380 publications
0
104
0
2
Order By: Relevance
“…ROS are discussed in the regulation of thermogenesis [ 20 , 21 , 22 ]. Meanwhile, stress and inflammation have been linked to the activation of the tryptophan (Trp)–kynurenine (KYN) metabolic system [ 78 ]. According to some researchers, revealing the link between mitochondrial biogenesis and the KYN metabolic system may be a promising option [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS are discussed in the regulation of thermogenesis [ 20 , 21 , 22 ]. Meanwhile, stress and inflammation have been linked to the activation of the tryptophan (Trp)–kynurenine (KYN) metabolic system [ 78 ]. According to some researchers, revealing the link between mitochondrial biogenesis and the KYN metabolic system may be a promising option [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, stress and inflammation have been linked to the activation of the tryptophan (Trp)–kynurenine (KYN) metabolic system [ 78 ]. According to some researchers, revealing the link between mitochondrial biogenesis and the KYN metabolic system may be a promising option [ 78 ]. Experimental data have shown that ROS production is increased in mice with knockout UCP3 [ 79 , 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms that have been found to be linked to depression also include a dysfunctional hypothalamic-pituitary-adrenal (HPA) axis [ 6 ], immune-inflammatory and oxidative pathways [ 7 ], altered vagus nerve tone [ 8 ], and imbalance between neural excitatory and inhibitory signaling [ 9 ]. Other factors that can lead to the development of depression includes chronic and acute stress [ 10 ], depletion of monoamines [ 11 ], poor nutrition [ 12 ], mitochondrial dysfunction [ 13 ], disrupted metabolism [ 14 ], environmental factors and epigenetics [ 15 ], infection [ 16 ], levels of sex hormones [ 17 ], etc. Inflammation is now considered one of the primary pathologies that lead to depression.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel kynurenine pathway (KP) has drawn attention in the cytokine theory [ 10 ]. Pro-inflammatory cytokines activate the KP by affecting tryptophan (TRP) metabolism and releasing neurotoxins, which can either reduce serotonin production or promote serotonin reuptake [ 13 ]. The COVID-19 pandemic has led to long-term psychiatric symptoms, possibly due to an immunological reaction to the virus itself, as well as fundamental changes in life associated with the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…According to the National Institute of Mental Health (NIMH) in 2021, the international prevalence rates are reportedly between 0.33–0.75%. There are various contributing factors to the development of schizophrenia, including genetic predisposition and polygenic risk [ 2 ], neuroinflammation [ 3 ], decreased synaptic spine density [ 4 ], cannabis use [ 5 ], psychosocial influences and reduced stress resilience [ 6 ], adverse childhood experiences and trauma [ 7 ], diminished anti-inflammatory response alongside reduced lipid metabolism [ 8 ], mitochondrial stress resilience [ 9 ], and gene–environment interaction effects [ 10 ]. In line with this, the diathesis–stress model may be a potential hypothesis accounting for the overall development of the disorder [ 11 ].…”
Section: Introductionmentioning
confidence: 99%